Simple modification measurement of photodegradability of polymers by using photo-induced chemiluminescence technique / Siti Farhana Zakaria and Keith R. Millington - Zakaria, Siti Farhana; Millington, Keith R. (Research Management Institute (RMI), 2013)
Polymers and organic materials that are exposed to sunlight undergo photooxidation, which leads to deterioration oftheir physical properties. To allow adequate performance under outdoor conditions, synthetic polymers require additives such as antioxidants and UV absorbers. A major problem with optimising polymer formulations to maximise their working life span is that accelerated weathering tests are empirical. The conditions differ significantly from real weathering situations, and samples require lengthy irradiation period. Degradation may not be apparent in the early stages of exposure, although this is when products such as hydroperoxides are formed which later cause acceleration ofoxidation. Asimple way ofquantifying the number of free radicals presents in organic materials following exposure to light or heat is by measuring chemiluminescence (CL) emission. Most polymers emit CL when they undergo oxidative degradation, and it originates from the bimolecular reaction of macroperoxy radicals which creates an excited carbonyl.